Traceless chelation-controlled rhodium-catalyzed intermolecular alkene and alkyne hydroacylation. - Hooper, J; Young, R; Weller, A; Willis, M (2013)
A new functional-group tolerant, rhodium-catalyzed, sulfide-reduction process is combined with rhodium-catalyzed chelation-controlled hydroacylation reactions to give a traceless hydroacylation protocol. Aryl- and alkenyl aldehydes can be combined with both alkenes, alkynes and allenes to give traceless products in high yields. A preliminary mechanistic proposal is also presented.